Distress predicts utilization of psychosocial health services in oncology patients. Issue 1 (29th October 2018) - Hamilton, Jessica; Kroska, Emily B.
Abstract: Objective: The prevalence of increased distress among cancer patients has been well established and is known to be associated with negative consequences. Limited research has examined the association between distress and utilization of services, however, which is critical to understanding whether measurements of distress are being used to optimize patient care in the context of cancer. Methods: One thousand two hundred thirteen adult cancer patients completed the Distress Thermometer and Patient Needs Assessment early in their cancer care. Electronic medical record (EMR)–abstracted data included psychosocial service utilization in the 12 months following the completion of these psychosocial metrics. Logistic regressions followed by t tests were completed to assess if distress or unmet needs were affiliated with service utilization rates. Results: When controlling for age, distress significantly predicted service utilization rates overall. Follow‐up t tests suggest that use of social work and registered dietician services was higher among those with distress scores greater than 6. When assessing unmet needs, utilization rates were positively associated with number of unmet needs, specifically for social work and dieticians. Conclusions: Distress and unmet needs were related to higher rates of psychosocial service utilization during the 12 months following assessment of symptoms. These results support the continued mandate for evaluation of distress and suggest that psychosocial screening may be assisting in directing referrals and enhancing comprehensive care for patients. As psychosocial services grow, the need for continued evaluation is recommended to determine if psychology and chaplaincy services are utilized at higher rates as available providers increase.